Cellulose micron sheet powder and preparation method of high-haze transparent film of cellulose micron sheet powder

Through hydrothermal-assisted preparation technology, the problems of irreversible agglomeration and poor redispersibility of cellulose micro-nano powders in the sulfuric acid hydrolysis method were solved, the preparation of high-haze transparent films was achieved, and the mechanical strength and optical properties of the films were improved.

CN120718310APending Publication Date: 2025-09-30SICHUAN UNIV

Patent Information

Application Number
CN202510796398.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-06-17
Filing Date
2025-06-16
Publication Date
2025-09-30

AI Technical Summary

Technical Problem

In the prior art, the process of preparing micro-nanocellulose by sulfuric acid hydrolysis has the problems of irreversible agglomeration and poor redispersibility during the concentration and dehydration of the suspension, resulting in high transportation costs and difficulty in application to film preparation.

Method used

A hydrothermal-assisted method was used to regulate the acidolysis and hydrothermal treatment conditions, and cellulose micron flake powder with uniform thickness was formed by freeze-drying, which was then compounded with polyvinyl alcohol to prepare a high-haze transparent film.

Benefits of technology

The problems of irreversible agglomeration and poor redispersibility of cellulose microsheets were solved, and powdered cellulose microsheets with excellent rehydration properties were obtained, which can be compounded with polyvinyl alcohol to form a high-haze transparent film, thereby improving the mechanical strength and optical properties of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120718310A_ABST
    Figure CN120718310A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of cellulose micron sheet powder and a high-haze transparent film thereof, which comprises the following steps: S1, crushing bamboo pulp foil to obtain a cellulose raw material; s2, placing in a sulfuric acid solution, stirring in an oil bath for hydrolysis, adding water after reaction, taking out, and placing in a polytetrafluoroethylene hydrothermal synthesis reaction kettle for auxiliary reaction to obtain a milk white suspension; s3, centrifuging and dialyzing the milk white suspension until the pH is nearly neutral; s4, performing ultrasonic treatment on a product in S3 by adopting an ultrasonic cell crusher, and performing freeze drying to obtain powdery cellulose micron sheets; according to the invention, through reasonable optimization of acidolysis and hydrothermal process parameters, the powdery cellulose micron sheet with uniform thickness and no irreversible keratinization defect is obtained, has excellent redispersibility after rehydration, can be compounded with polyvinyl alcohol to form a high-haze transparent film, and overcomes the defect that in the subsequent drying process of sulfuric acid hydrolysis of micro-nano cellulose, the film is not easy to form, and the film is not easy to form. The problems of irreversible agglomeration and poor rehydration redispersibility caused by hydrogen bond induction are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cellulose, in particular to a method for preparing cellulose micron flake powder and a high-fog transparent film thereof. Background Art

[0002] Micro- and nano-cellulose possesses properties such as light weight, high specific surface area, high aspect ratio, high surface chemical activity, and low thermal expansion coefficient. It is considered a next-generation composite material reinforcement phase with broad application prospects in numerous fields, including water treatment, energy, sensing, electromagnetic shielding, and biomedicine. Typically, chemical or biological pretreatment is combined with mechanical methods (such as high-pressure homogenization, ultrasound, and ball milling) to produce micro- and nano-cellulose with varying morphologies. Sulfuric acid hydrolysis is the most classic chemical method. Sulfuric acid dissociates into protonated ions, which diffuse into the amorphous regions of cellulose, decomposing the glycosidic bonds of the cellulose chains and replacing some of the hydroxyl groups with sulfonic acid groups, thereby producing sulfated cellulose.

[0003] Sulfated cellulose nanocrystals have a one-dimensional, rigid, rod-like morphology, and their suspensions can be dispersed stably and evenly in a durable, stable, and low-concentration dispersion. Low-concentration dispersions of these nanocrystals are the primary method for preparing sulfated cellulose materials. However, due to the strong hydrogen-bonding network formed by the numerous hydroxyl groups on the cellulose surface, micro- and nano-celluloses experience irreversible aggregation during concentration, dehydration, or drying, making them difficult to redisperse in water. This severely hinders the storage and transportation of sulfated micro- and nano-celluloses, as well as their preparation and application in high-value-added products.

[0004] To address these issues, Chinese invention patent CN114685812A discloses a method for efficiently concentrating and redispersing micro / nanocellulose. The method comprises the following steps: adding polyvinyl pyrrolidone to a micro / nanocellulose suspension and stirring to obtain a mixed suspension; concentrating and dehydrating the suspension, adding polyvinyl pyrrolidone to the initial amount, then diluting the suspension with water, and then performing ultrafine grinding and redispersion to obtain a micro / nanocellulose suspension. Although a high polyvinyl pyrrolidone dosage can increase the concentration of the micro / nanocellulose suspension, it can cause severe flocculation of the micro / nanocellulose, reducing the degree of dispersion and the light transmittance of the suspension.

[0005] Chinese invention patent number CN117510910A discloses a redispersible nanocellulose powder and its preparation method. This invention uses a precipitant to concentrate nanocellulose from an aqueous suspension. An alcohol dispersant, such as n-butanol, with a boiling point higher than water, is added to the concentrated nanocellulose. The water and precipitant are then preferentially evaporated from the nanocellulose dispersion by rotary evaporation or oven heating, allowing the nanocellulose to dry into a powder in a pure dispersant. However, using too little precipitant prevents the nanocellulose from completely settling, affecting the yield. Using too much precipitant increases the difficulty of decomposing and removing the precipitant during evaporation.

[0006] Therefore, it is necessary to develop a redispersible micro-nanocellulose powder that does not require additional additives and is easy to prepare based on the preparation of micro-nanocellulose by sulfuric acid hydrolysis, so as to solve the structural defects of irreversible agglomeration and poor redispersibility during suspension concentration and dehydration, save transportation costs and be conveniently used in film preparation. Summary of the Invention

[0007] The present invention overcomes the shortcomings of the existing technology and provides a method for preparing cellulose micron sheet powder and a high-haze transparent film thereof. The method adopts a hydrothermal-assisted method based on the sulfuric acid hydrolysis method, and by regulating the acidolysis and hydrothermal treatment conditions, freeze-drying is performed to form powdered cellulose micron sheets with uniform thickness and a non-porous structure. The cellulose micron sheets have excellent rehydration dispersibility and can be compounded with polyvinyl alcohol to obtain a high-haze transparent film.

[0008] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing cellulose micron flake powder and a high-haze transparent film thereof, comprising the following steps:

[0009] S1, mechanically crushing bamboo pulp foil to a certain mesh size to obtain a cellulose raw material;

[0010] S2, placing cellulose in a sulfuric acid solution, stirring in an oil bath at 40-55°C for hydrolysis, adding a certain volume of water to the reaction solution after the reaction, taking out the solution and placing it in a polytetrafluoroethylene hydrothermal synthesis reactor for auxiliary reaction to obtain a milky white suspension after the reaction;

[0011] S3, centrifuging the milky white suspension after the reaction and dialyzing it until the pH is close to neutral;

[0012] S4, ultrasonically treating the product in S3 with an ultrasonic cell disruptor, and freeze-drying the product to obtain powdered cellulose micron sheets;

[0013] S5. Add a certain amount of water to the cellulose microsheets, perform ultrasonic dispersion, add polyvinyl alcohol, stir and cross-link, and place in a constant temperature box for drying using a solution casting method to obtain a high-haze transparent composite film.

[0014] In a preferred embodiment of the present invention, in step S1, the mechanical crushing is one or more of extrusion, bending, splitting, grinding or impact; the mesh size of the cellulose raw material is 100-300 mesh, for example, it can be 100 mesh, 120 mesh, 140 mesh, 160 mesh, 180 mesh, 200 mesh, 220 mesh, 240 mesh, 260 mesh, 280 mesh or 300 mesh, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0015] In a preferred embodiment of the present invention, in step S2, the concentration of the sulfuric acid solution is 50-70 wt%, for example, it can be 50 wt%, 52 wt%, 54 wt%, 56 wt%, 58 wt%, 60 wt%, 62 wt%, 64 wt%, 66 wt%, 68 wt% or 70 wt%, but is not limited to the listed values. Other values ​​not listed within this numerical range are also applicable; the mass ratio of the sulfuric acid solution to the cellulose is 12-15:1.

[0016] In a preferred embodiment of the present invention, in the step S2, the hydrolysis reaction time is 15 to 30 min, for example, it can be 15 min, 18 min, 21 min, 24 min, 27 min or 30 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable; the hydrothermal reaction temperature is 100 to 120 ° C, for example, it can be 100 ° C, 104 ° C, 108 ° C, 112 ° C, 116 ° C or 120 ° C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0017] In a preferred embodiment of the present invention, in the step S3, the centrifugal speed of the milky suspension is 6000-10000 r / min, for example, it can be 6000 r / min, 6400 r / min, 6800 r / min, 7200 r / min, 7600 r / min, 8000 r / min, 8400 r / min, 8800 r / min, 9200 r / min, 9600 r / min or 10000 r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable; the centrifugation time is 8-15 min, for example, it can be 8 min, 9 min, 11 min, 13 min or 15 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable; the dialysis process is assisted by magnetic stirring to accelerate acid removal.

[0018] In a preferred embodiment of the present invention, in the step S4, the ultrasonic cell disruptor is of model JY98-IIIDN, with a rated power of 1200 W, and the power of the ultrasonic treatment is 2% to 6%, for example, it can be 2%, 2.4%, 2.8%, 3.2%, 3.6%, 4%, 4.4%, 4.8%, 5.2%, 5.6% or 6%, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable, and the ultrasonic switching time is 5 s.

[0019] In a preferred embodiment of the present invention, in the step S4, the freeze-drying temperature is -30°C and the processing time is 36 to 72 hours, for example, it can be 36 hours, 40 hours, 44 hours, 48 ​​hours, 52 hours, 56 hours, 60 hours, 64 hours, 68 hours or 72 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] In a preferred embodiment of the present invention, in the step S5, the concentration of the cellulose microsheet dispersion is 0.8 to 1.3 wt%, for example, it can be 0.8 wt%, 0.9 wt%, 1.0 wt%, 1.1 wt%, 1.2 wt% or 1.3 wt%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the ultrasonic treatment time is 5 to 15 min, for example, it can be 5 min, 7 min, 9 min, 11 min, 13 min or 15 min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0021] In a preferred embodiment of the present invention, in step S5, the concentration of the polyvinyl alcohol aqueous solution is 8 to 15 wt%, for example, 8 wt%, 10 wt%, 11 wt%, 13 wt% or 15 wt%, but is not limited to the listed values. Other values ​​not listed within this numerical range are also applicable; the mass ratio of the cellulose microsheets to the polyvinyl alcohol is 1:0.5 to 1.5.

[0022] In a preferred embodiment of the present invention, in the step S5, the temperature of the constant temperature box is 30-40°C, for example, it can be 30°C, 32°C, 34°C, 36°C, 38°C or 40°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable; the drying treatment time is 18-36h, for example, it can be 18h, 20h, 22h, 24h, 26h, 28h, 30h, 32h, 34h or 36h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] The present invention solves the defects existing in the background technology and has the following beneficial effects:

[0024] (1) The present invention provides a method for preparing cellulose micron flake powder and a high-haze transparent film thereof. By rationally optimizing the acid hydrolysis and hydrothermal process parameters, powdered cellulose micron flakes with uniform thickness and no irreversible keratinization defects are obtained. The powdered cellulose micron flakes have excellent redispersibility after rehydration and can form a high-haze transparent film when compounded with polyvinyl alcohol. This overcomes the problems of irreversible agglomeration and poor rehydration redispersibility caused by hydrogen bonding during the subsequent drying of micro-nanocellulose after sulfuric acid hydrolysis.

[0025] (2) In the present invention, a reasonable ultrasonic time is used in the preparation of cellulose microsheets to maintain a better aspect ratio of the cellulose microsheets. Ultrasound can effectively disperse cellulose fragments and affect their structure. By generating high-frequency sound waves, cavitation effects, microjets and shock waves are generated in the liquid. These effects can destroy the hydrogen bonds and other interaction forces between cellulose molecules, making it easier to disperse and refine. A better aspect ratio means that it has a better aspect ratio. Since the cellulose microsheets can be better interwoven and supported with each other in the high-haze transparent film, the mechanical strength and toughness of the high-haze transparent film can be enhanced. At the same time, it will affect the transparency and scattering properties of the film, help scatter light, and thus improve the light transmittance and haze of the film.

[0026] (3) In the present invention, the size of the cellulose particles after pulverization is determined by pulverizing the cellulose raw material to a certain mesh number. A higher mesh number means finer particles, thereby producing thinner cellulose microsheets, which will have better dispersibility and performance in subsequent applications. Smaller particles are subject to less gravitational sedimentation force, which is conducive to forming a more uniform cellulose suspension and the final high-haze transparent film in the subsequent preparation process. In addition, when preparing cellulose microsheets, more uniform and more uniformly sized microsheets can be formed. The increased surface area of ​​the particles is conducive to the effective contact between sulfuric acid and cellulose in subsequent chemical reactions (such as hydrolysis reactions), thereby improving the reaction efficiency. At the same time, smaller cellulose particles may be easier to handle during ultrasonic treatment and freeze-drying, and are more easily dispersed by ultrasonic waves and dried from a frozen state. The finer particle size of the cellulose raw material shortens the distance between cellulose molecules and enhances the intermolecular interaction, which can promote the reorganization and aggregation of cellulose molecular chains, thereby forming cellulose microsheets with specific structure and performance, so that the cellulose microsheets can be more evenly dispersed in the substrate when preparing the film. The prepared high-haze transparent film has a more uniform structure, higher mechanical strength and better optical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments described in the present invention. Those skilled in the art can also derive other drawings based on these drawings without inventive efforts.

[0028] Figure 1 This is a photo of the micron flake powder and its rehydrated dispersion prepared in Example 1 of the present invention;

[0029] Figure 2These are photos of the high-haze transparent composite film prepared in Example 1 of the present invention in a flat state (attached to the surface of a finger) and in a suspended state (with a gap between the finger and the film);

[0030] Figure 3 1 is a scanning electron microscope (SEM) macroscopic and microscopic image of the cellulose microsheet prepared in Example 1 of the present invention;

[0031] Figure 4 1. The scanning electron microscope (SEM) macroscopic and microscopic images of the cellulose microsheet prepared in Example 2 of the present invention;

[0032] Figure 5 These are the scanning electron microscope (SEM) macroscopic and microscopic images of the cellulose microsheet prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0033] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0034] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the scope of protection of the present invention is not limited to the specific embodiments disclosed below.

[0035] It should be noted that the raw materials, equipment, reagents, etc. used in the present invention can be purchased from the market or obtained through existing preparation methods.

[0036] A method for preparing cellulose micron flake powder and a high-haze transparent film thereof comprises the following steps:

[0037] S1, mechanically crushing bamboo pulp foil to a certain mesh size to obtain a cellulose raw material;

[0038] S2, placing cellulose in a sulfuric acid solution, stirring in an oil bath at 40-55°C for hydrolysis, adding a certain volume of water to the reaction solution after the reaction, taking out the solution and placing it in a polytetrafluoroethylene hydrothermal synthesis reactor for auxiliary reaction to obtain a milky white suspension after the reaction;

[0039] S3, centrifuging the milky white suspension after the reaction and dialyzing it until the pH is close to neutral;

[0040] S4, ultrasonically treating the product in S3 with an ultrasonic cell disruptor, and freeze-drying the product to obtain powdered cellulose micron sheets;

[0041] S5. Add a certain amount of water to the cellulose microsheets, perform ultrasonic dispersion, add polyvinyl alcohol, stir and cross-link, and place in a constant temperature box for drying using a solution casting method to obtain a high-haze transparent composite film.

[0042] In some specific embodiments, in step S1, the mechanical crushing is one or more of extrusion, bending, splitting, grinding or impact; and the mesh size of the cellulose raw material is 100-300 mesh.

[0043] In some specific embodiments, in step S2, the concentration of the sulfuric acid solution is 50-70 wt%, the mass ratio of the sulfuric acid solution to the cellulose is 12-15:1; the hydrolysis reaction time is 15-30 min, and the hydrothermal reaction temperature is 100-120°C.

[0044] In some specific embodiments, in step S3, the milky white suspension is centrifuged at a speed of 6000-10000 r / min for 8-15 min; and the dialysis process is supplemented with magnetic stirring to accelerate acid removal.

[0045] In some specific embodiments, in step S4, the ultrasonic cell disruptor is of model JY98-IIIDN, with a rated power of 1200 W, a frequency of 20 kHz, a power adjustment range of 1-100%, an ultrasonic treatment power of 2% to 6%, an ultrasonic switch time of 5 s, and an ultrasonic treatment time of 15 to 30 min; the freeze-drying temperature is -30°C, and the treatment time is 36 to 72 h.

[0046] In some specific embodiments, in step S5, the concentration of the cellulose microsheet dispersion is 0.8-1.3 wt %, and the ultrasonic treatment time is 5-15 min; the concentration of the polyvinyl alcohol aqueous solution is 8-15 wt %, and the mass ratio of cellulose microsheet to polyvinyl alcohol is 1:0.5-1.5; the temperature of the constant temperature box is 30-40° C., and the drying treatment time is 18-36 h.

[0047] Example 1

[0048] A method for preparing cellulose micron flake powder and a high-haze transparent film thereof comprises the following steps:

[0049] S1, mechanically crushing bamboo pulp foil into 220 meshes to obtain cellulose raw material;

[0050] S2, placing the cellulose in a 64 wt% sulfuric acid solution, stirring and hydrolyzing in an oil bath at 45°C for 15 min, wherein the mass ratio of the sulfuric acid solution to the cellulose is 13.5:1, adding water twice the volume of the reaction solution after the reaction, taking out and placing in a polytetrafluoroethylene hydrothermal synthesis reactor, auxiliary reaction at 110°C for 15 min, to obtain a milky white suspension after the reaction;

[0051] S3, the milky white suspension after the reaction was centrifuged at 8000 r / min for 10 min, after discarding part of the supernatant, dialyzed to a pH close to neutral, and the dialysis process was supplemented with magnetic stirring to accelerate the removal of acid;

[0052] S4. Ultrasonic cell disruptor was used to treat the product in S3 at 60W power for 15 min to obtain a white cellulose flake dispersion, which was freeze-dried at -30°C for 36 h to remove moisture and obtain powdered cellulose micron flakes.

[0053] S5. Add a certain amount of water to the cellulose microsheet to form a dispersion with a concentration of 1.0 wt%. After ultrasonic dispersion for 10 minutes, add a 10 wt% polyvinyl alcohol aqueous solution and stir at room temperature for cross-linking for 1 hour. The mass ratio of cellulose microsheet to polyvinyl alcohol is 1:1. Use the solution casting method to place it in a constant temperature box at 35°C and dry it for 18 hours to obtain a high-haze transparent composite film.

[0054] Example 2

[0055] This example is basically the same as Example 1, except that: Step S4 is as follows: the product in S3 is ultrasonically treated with an ultrasonic cell disruptor at a power of 60 W for 25 minutes to obtain a white flaky cellulose dispersion, which is then freeze-dried at -30°C for 36 hours to remove moisture and obtain powdered cellulose micron sheets.

[0056] Example 3

[0057] This example is basically the same as Example 1, except that: Step S4 is as follows: the product in S3 is ultrasonically treated at a power of 60 W for 30 minutes using an ultrasonic cell disruptor to obtain a white flaky cellulose dispersion, which is then freeze-dried at -30°C for 36 hours to remove moisture and obtain powdered cellulose microsheets.

[0058] In order to verify the successful acquisition of the cellulose microsheets in Examples 1-3, Figure 1 Shown in the figure is a photo of the micron flake powder and its rehydrated dispersion prepared in Example 1 of the present invention; Figure 2 ] are actual photos of the high-haze transparent composite film prepared in Example 1 of the present invention in a flat state (attached to the surface of a finger) and in a suspended state (with a gap between the finger and the film); Figure 3 Shown in the figure are the scanning electron microscope (SEM) macroscopic and microscopic images of the cellulose microsheet prepared in Example 1 of the present invention; Figure 4 Shown in the figure are the scanning electron microscope (SEM) macroscopic and microscopic images of the cellulose microsheet prepared in Example 2 of the present invention; Figure 5 Shown in the figure are the scanning electron microscope (SEM) macroscopic and microscopic images of the cellulose microsheet prepared in Example 3 of the present invention.

[0059] Comparative Example 1

[0060] This comparative example is basically the same as Example 1, except that: Step S4 is as follows: the product in S3 is ultrasonically treated with an ultrasonic cell disruptor at a power of 60 W for 40 minutes to obtain a white flaky cellulose dispersion, which is then freeze-dried at -30°C for 36 hours to remove moisture and obtain powdered cellulose micron sheets.

[0061] Comparative Example 2

[0062] This comparative example is basically the same as Example 1, except that: Step S4 is as follows: the product in S3 is ultrasonically treated with an ultrasonic cell disruptor at a power of 60 W for 8 minutes to obtain a white flaky cellulose dispersion, which is then freeze-dried at -30°C for 36 hours to remove moisture and obtain powdered cellulose micron sheets.

[0063] Comparative Example 3

[0064] This comparative example is basically the same as Example 1, except that: Step S1 is: mechanically crushing the bamboo pulp foil to 100 mesh to obtain a cellulose raw material.

[0065] Comparative Example 4

[0066] This comparative example is basically the same as Example 1, except that: Step S1 is: mechanically crushing the bamboo pulp foil to 300 meshes to obtain a cellulose raw material.

[0067] Comparative Example 5

[0068] This comparative example is basically the same as Example 1, except that: Step S1 is: mechanically crushing the bamboo pulp foil into 80 meshes to obtain a cellulose raw material.

[0069] Comparative Example 6

[0070] This comparative example is basically the same as Example 1, except that: Step S1 is: mechanically crushing the bamboo pulp foil to 350 meshes to obtain a cellulose raw material.

[0071] Comparative Example 7

[0072] This comparative example is basically the same as Example 1, except that: Step S2 comprises placing cellulose in a 50 wt% sulfuric acid solution, stirring and hydrolyzing in an oil bath at 45°C for 15 minutes, wherein the mass ratio of the sulfuric acid solution to the cellulose is 13.5:1; adding water twice the volume of the reaction solution after the reaction; and removing the cellulose from the cellulose and placing the cellulose in a polytetrafluoroethylene hydrothermal synthesis reactor for auxiliary reaction at 110°C for 15 minutes to obtain a milky white suspension after the reaction.

[0073] Comparative Example 8

[0074] This comparative example is basically the same as Example 1, except that: Step S2 comprises placing cellulose in a 70 wt% sulfuric acid solution, stirring and hydrolyzing in an oil bath at 45°C for 15 minutes, wherein the mass ratio of the sulfuric acid solution to the cellulose is 13.5:1; adding water twice the volume of the reaction solution after the reaction; and removing the cellulose from the cellulose and placing the cellulose in a polytetrafluoroethylene hydrothermal synthesis reactor for auxiliary reaction at 110°C for 15 minutes to obtain a milky white suspension after the reaction.

[0075] Comparative Example 9

[0076] This comparative example is basically the same as Example 1, except that: Step S2 comprises placing cellulose in a 43 wt% sulfuric acid solution, stirring and hydrolyzing in an oil bath at 45° C. for 15 min, wherein the mass ratio of the sulfuric acid solution to the cellulose is 13.5:1; adding water twice the volume of the reaction solution after the reaction; and removing the cellulose from the cellulose and placing the cellulose in a polytetrafluoroethylene hydrothermal synthesis reactor for auxiliary reaction at 110° C. for 15 min to obtain a milky white suspension after the reaction.

[0077] Comparative Example 10

[0078] This comparative example is basically the same as Example 1, except that: Step S2 comprises placing cellulose in a 75 wt% sulfuric acid solution, stirring and hydrolyzing in an oil bath at 45°C for 15 minutes, wherein the mass ratio of the sulfuric acid solution to the cellulose is 13.5:1; adding water twice the volume of the reaction solution after the reaction; and removing the cellulose from the cellulose and placing the cellulose in a polytetrafluoroethylene hydrothermal synthesis reactor for auxiliary reaction at 110°C for 15 minutes to obtain a milky white suspension after the reaction.

[0079] Comparative Example 11

[0080] This comparative example is basically the same as Example 1, except that: Step S2 comprises placing cellulose in a 64 wt% sulfuric acid solution, stirring and hydrolyzing in an oil bath at 45°C for 15 min, wherein the mass ratio of the sulfuric acid solution to the cellulose is 13.5:1, and adding water twice the volume of the reaction solution after the reaction to obtain a milky white suspension after the reaction.

[0081] In order to evaluate the specific technical effects of the preparation methods of the cellulose micron sheet powders of Examples 1-3 and Comparative Examples 1-11, statistical calculations were performed on the structural integrity, average thickness, and aspect ratio of the cellulose micron sheets prepared in Examples 1-3 and Comparative Examples 1-11. The results are shown in Table 1.

[0082] The tensile strength of the high-haze transparent composite films prepared in Examples 1-3 and Comparative Examples 1-11 was measured with reference to GB / T 1040.3-2006 "Determination of tensile properties of plastics", the transmittance and haze were measured with reference to GB / T 2410-2008 "Determination of transmittance and haze of transparent plastics", and the roughness was measured using a roughness meter. The results are shown in Table 2.

[0083] Table 1:

[0084]

[0085]

[0086] Table 2:

[0087]

[0088]

[0089] As shown in Table 1 and Table 2, Figure 1-5 It can be seen that the cellulose microsheets obtained in Examples 1-3 have uniform thickness, all within 2 μm, without structural defects, and are in powder form. There is no irreversible agglomeration phenomenon after rehydration, and a stable milky white dispersion can be formed. The high-haze transparent composite film has good mechanical and optical properties. By comparing Examples 1-3 with Comparative Examples 1 and 2, it can be seen that different ultrasonic times have little effect on the thickness of the cellulose microsheets, but have a greater effect on their aspect ratio. Ultrasound can effectively disperse cellulose fragments and affect their structure. By generating high-frequency sound waves, cavitation effects, microjets and shock waves are generated in the liquid. These effects can destroy the hydrogen bonds and other interaction forces between cellulose molecules, making it easier to disperse and refine. When the ultrasonic time is too long, although the cellulose fragments can be further refined, it will also lead to excessive degradation and over-dispersion, making the cellulose fragments smaller, forming finer nano-scale particles, and losing directionality in the solution, resulting in the length and width of the formed cellulose microsheets. The aspect ratio decreases; when the ultrasonic time is too short, it is not enough to completely destroy the interaction force between cellulose molecules, so that the cellulose fragments still maintain a long shape when forming microsheets, and the cellulose fragments are not fully dispersed and refined, resulting in the formed cellulose microsheets with a larger aspect ratio; the aspect ratio can affect the arrangement and orientation of cellulose microsheets in the composite film, thereby affecting the performance of the composite film. Cellulose microsheets with higher aspect ratios are more likely to interweave and stack with each other in the film, forming a tighter network structure, thereby improving the mechanical strength of the composite film, and also affecting the scattering and refraction behavior of cellulose microsheets to light, thereby affecting the haze and transparency of the composite film. Cellulose microsheets with too small aspect ratios will tend to be arranged in parallel in the film, which will reduce the haze of the film because light can pass through more easily without sufficient scattering. Cellulose microsheets with too large aspect ratios will more easily agglomerate in the film to form an uneven structure, resulting in a decrease in the transparency of the film and even obvious structural defects.

[0090] By comparing Example 1 with Comparative Examples 3 and 4, it can be seen that the mesh number determines the size of the cellulose particles after crushing. A higher mesh number means finer particles, thereby producing thinner cellulose microsheets, which will have better dispersibility and performance in subsequent applications. Smaller particles are subject to less gravitational sedimentation force, which is conducive to forming a more uniform cellulose suspension and a final high-haze transparent film in the subsequent preparation process, and thus, when preparing cellulose microsheets, more uniform and more uniformly sized microsheets can be formed. The increased surface area of ​​the particles is conducive to the effective contact between sulfuric acid and cellulose in subsequent chemical reactions (such as hydrolysis reactions), thereby improving the reaction efficiency. At the same time, smaller cellulose particles may be easier to handle during ultrasonic treatment and freeze-drying, and are more easily dispersed by ultrasonic waves and dried from a frozen state. Finer cellulose raw material particle size shortens the distance between cellulose molecules and enhances intermolecular interactions, which can promote the reorganization and aggregation of cellulose molecular chains, thereby forming cellulose microsheets with specific structures and properties, so that the cellulose microsheets can be more evenly dispersed in the substrate when preparing the film. The films prepared from the raw materials often have a more uniform structure, higher mechanical strength and better optical properties. By comparing Example 1 with Comparative Examples 5 and 6, it can be seen that when the crushed particles are too small (the mesh number is too high), the cellulose microsheets are too fine. The too small particle size may increase the tendency of the cellulose microsheets to agglomerate, affecting their dispersibility and stability in subsequent applications. Since the cellulose microsheets are too fine, it may be difficult to form a uniform network structure when preparing the film, affecting the mechanical and optical properties of the film, resulting in a decrease in the transparency of the film and an increase in its surface roughness. When the crushed particles are too large (the mesh number is too low), during acid hydrolysis, sulfuric acid is difficult to fully penetrate into the cellulose molecular chains, resulting in incomplete cellulose degradation. The cellulose microsheets formed are large and uneven in size, resulting in an excessively thick cellulose sheet layer, which is not conducive to subsequent dispersion and cross-linking reactions, and affects the haze and transparency of the final film. Since the cellulose microsheets are large and uneven in size, agglomeration and defects appear in the film, affecting its overall performance and appearance. Large cellulose microsheets will reduce the mechanical properties of the film and increase its surface roughness.

[0091] By comparing Example 1 with Comparative Examples 7 and 8, it can be seen that sulfuric acid acts as a catalyst in the cellulose degradation process. Its strong acidity promotes the breakage and degradation of cellulose molecular chains. Sulfuric acid can more effectively destroy the hydrogen bonds between cellulose molecules, thereby promoting the depolymerization of cellulose. Appropriate acid hydrolysis can effectively promote the degradation and refinement of cellulose, forming cellulose micron sheets with uniform size and regular shape. When preparing the film subsequently, the sheets can be evenly dispersed in the substrate to form a high-haze transparent composite film with a tight structure and excellent performance. At the same time, the acid hydrolysis of sulfuric acid will destroy the chemical bonds in the cellulose raw material, causing it to degrade into smaller fragments. The concentration of sulfuric acid and the mass ratio of sulfuric acid to cellulose raw material will affect the degree of acid hydrolysis and the size of the product, thereby affecting the quality of the cellulose micron sheet. Aspect ratio, higher sulfuric acid concentration and longer acid hydrolysis time may lead to stronger degradation and produce smaller fragments, which may reduce the aspect ratio of the cellulose microsheets. By comparing Example 1 with Comparative Examples 9 and 10, it can be seen that when the sulfuric acid concentration is too low, the cellulose cannot be fully degraded, resulting in the cellulose microsheets being larger in size and irregular in shape, and then easily forming agglomerates and defects in the subsequent preparation of the film, affecting the uniformity and performance of the film. When the sulfuric acid concentration is too high, the degradation rate of cellulose will be accelerated, resulting in the morphology of the cellulose microsheets changing from a long filamentous structure to a short rod-like structure, affecting its dispersibility and cross-linking properties in the film, which will not only affect the size and shape of the cellulose microsheets, but also affect its dispersibility and mechanical properties in the subsequent film.

[0092] By comparing Example 1 with Comparative Example 11, it can be seen that hydrothermal assistance can destroy the hydrogen bonds and glycosidic bonds in the cellulose molecular chain, making it easier for cellulose to be degraded into smaller fragments. In the hydrothermal environment of high temperature and high pressure, the movement of water molecules is intensified, and they can more effectively penetrate into the cellulose molecular chain and form hydrogen bonds with the hydroxyl groups on the cellulose molecular chain. The formation and breaking of hydrogen bonds can promote the breaking and reorganization of the cellulose molecular chain, thereby obtaining cellulose micron sheets with smaller size and more uniform structure. Hydrothermal assisted treatment can degrade cellulose more thoroughly, so the obtained cellulose micron sheets are smaller in size and more evenly distributed. These evenly distributed cellulose micron sheets can form a denser network structure in the subsequent preparation of thin films, thereby improving the mechanical and optical properties of the film. When there is no hydrothermal assistance, ultrasonic cell disruption The final liquid products are all light blue cellulose nanocrystal dispersions. During the freeze-drying process, the irreversible aggregation induced by hydrogen bonds forms keratinized defective flakes, which are difficult to ultrasonically disperse in water. The degradation and hydrolysis process of cellulose mainly depends on the catalytic effect of sulfuric acid. Without a high temperature and high pressure environment, the degradation rate of cellulose is slow and the degradation degree is limited. Without hydrothermal assistance, the movement of water molecules is weak, and it is difficult to effectively penetrate into the cellulose molecular chain and form hydrogen bonds with the hydroxyl groups on the cellulose molecular chain, making the cellulose micron flakes larger in size and unevenly distributed, and there will be more impurities and pigments. It is easy to form agglomerations and defects in the subsequent preparation of thin films, affecting the uniformity and performance of the film. In addition, due to the high content of impurities and pigments in the cellulose micron flakes, the light transmittance and color of the film will also be affected.

[0093] The present invention obtains powdered cellulose micron sheets with uniform thickness and no irreversible keratinization defects through reasonable optimization of acid hydrolysis and hydrothermal process parameters. The sheets have excellent redispersibility after rehydration and can form a transparent film with high haze when compounded with polyvinyl alcohol. This overcomes the problems of irreversible agglomeration and poor redispersibility after rehydration caused by hydrogen bonds induced during the subsequent drying of micro-nanocellulose after sulfuric acid hydrolysis.

[0094] The above description is based on the ideal embodiment of the present invention. It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the present invention. Therefore, the embodiments should be considered as illustrative and non-restrictive in all respects. The scope of the present invention is defined by the appended claims, not the foregoing description, and it is intended that all variations within the meaning and range of equivalents of the claims be encompassed within the present invention. Any reference signs in the claims should not be construed as limiting the claim to which they relate.

[0095] In addition, it should be understood that although this specification is described in terms of implementation methods, not every implementation method contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.

Claims

1. A method for preparing cellulose micron flake powder and a high-haze transparent film thereof, characterized in that: The following steps are involved: S1, mechanically crushing bamboo pulp foil to a certain mesh size to obtain a cellulose raw material; S2, placing cellulose in a sulfuric acid solution, stirring in an oil bath at 40-55°C for hydrolysis, adding a certain volume of water to the reaction solution after the reaction, taking out the solution and placing it in a polytetrafluoroethylene hydrothermal synthesis reactor for auxiliary reaction to obtain a milky white suspension after the reaction; S3, centrifuging the milky white suspension after the reaction and dialyzing it until the pH is close to neutral; S4, ultrasonically treating the product in S3 with an ultrasonic cell disruptor, and freeze-drying the product to obtain powdered cellulose micron sheets; S5. Add a certain amount of water to the cellulose microsheets, perform ultrasonic dispersion, add polyvinyl alcohol, stir and cross-link, and place in a constant temperature box for drying using a solution casting method to obtain a high-haze transparent composite film.

2. The method for preparing a cellulose micron flake powder and a high-haze transparent film thereof according to claim 1, characterized in that: In step S1, the mechanical crushing is one or more of extrusion, bending, splitting, grinding or impact; and the mesh size of the cellulose raw material is 100 to 300 meshes.

3. The method for preparing the cellulose micron flake powder and the high-haze transparent film thereof according to claim 1, characterized in that: In step S2, the concentration of the sulfuric acid solution is 50-70 wt%, and the mass ratio of the sulfuric acid solution to the cellulose is 12-15:

1.

4. The method for preparing the cellulose micron flake powder and the high-haze transparent film thereof according to claim 1, characterized in that: In step S2, the hydrolysis reaction time is 15 to 30 minutes, and the hydrothermal reaction temperature is 100 to 120°C.

5. The method for preparing the cellulose micron flake powder and the high-haze transparent film thereof according to claim 1, characterized in that: In step S3, the milky white suspension is centrifuged at a speed of 6000 to 10000 r / min for 8 to 15 min. The dialysis process is supplemented by magnetic stirring to accelerate acid removal.

6. The method for preparing the cellulose micron flake powder and the high-haze transparent film thereof according to claim 1, characterized in that: In the step S4, the ultrasonic cell disruptor is of model JY98-IIIDN, with a rated power of 1200W, the power of the ultrasonic treatment is 2% to 6%, and the ultrasonic switching time is 5s.

7. The method for preparing the cellulose micron flake powder and the high-haze transparent film thereof according to claim 1, characterized in that: In step S4, the freeze-drying temperature is -30°C and the processing time is 36 to 72 hours.

8. The method for preparing the cellulose micron flake powder and the high-haze transparent film thereof according to claim 1, characterized in that: In the step S5, the concentration of the cellulose microsheet dispersion is 0.8 to 1.3 wt %, and the ultrasonic treatment time is 5 to 15 minutes.

9. The method for preparing the cellulose micron flake powder and the high-haze transparent film thereof according to claim 1, characterized in that: In the step S5, the concentration of the polyvinyl alcohol aqueous solution is 8-15 wt %, and the mass ratio of the cellulose microsheets to the polyvinyl alcohol is 1:0.5-1.

5.

10. The method for preparing the cellulose micron flake powder and the high-haze transparent film thereof according to claim 1, characterized in that: In the step S5, the temperature of the constant temperature box is 30-40° C., and the drying treatment time is 18-36 hours.

Citation Information

Patent Citations

  • Method for efficiently concentrating and redispersing micro / nano cellulose

    CN114685812A

  • Redispersible nanocellulose powder and preparation method thereof

    CN117510910A

Cited By

  • High-light-transmittance low-haze bamboo holocellulose film and preparation method thereof

    CN121930519A